Development of Species-Specific SCAR Markers, Based on a SCoT Analysis, to Authenticate Physalis (Solanaceae) Species - Feng, Shangguo; Zhu, Yujia; Yu, Chenliang; Jiao, Kaili; Jiang, Mengying; Lu, Jiangjie; Shen, Chenjia; Ying, Qicai; Wang, Huizhong (Frontiers in Genetics, 2018)
Physalis is an important genus in the Solanaceae family. It includes many species of significant medicinal value, edible value and ornamental value. However, many Physalis species are easily confused because of their similar morphological traits, which hinder the utilization and protection of Physalis resources. Therefore, it is necessary to create fast, sensitive, and reliable methods for the Physalis species authentication. Intended for that, in this study, species-specific sequence-characterized amplified region (SCAR) markers were developed for accurate identification of the closely related Physalis species P. angulata, P. minima, P. pubescens, and P. alkekengi var. franchetii, based on a simple and novel marker system, start codon targeted (SCoT) marker. Thirty-four selected SCoT primers yielded 289 reliable SCoT loci, of which 265 were polymorphic. Four species-specific SCoT fragments (SCoT3-1404, SCoT3-1589, SCoT5-550, and SCoT36-520) from Physalis species were successfully identified, cloned, and sequenced. Based on these selected specific DNA fragments, four SCAR primers pairs were developed and named ST3KZ, ST3MSJ, ST5SJ, and ST36XSJ. PCR analysis of each of these primer pairs clearly demonstrated a specific amplified band in all samples of the target Physalis species, but no amplification was observed in other Physalis species. Therefore, the species-specific SCAR primer pairs developed in this study could be used as powerful tools that can rapidly, effectively, and reliably identify and differentiate Physalis species.